2010
DOI: 10.1093/humrep/deq069
|View full text |Cite
|
Sign up to set email alerts
|

Direct proportional relationship between endometrioma size and ovarian parenchyma inadvertently removed during cystectomy, and its implication on the management of enlarged endometriomas

Abstract: background: The aim of this study was to estimate whether or not the size of an endometrioma is related to the thickness of the ovarian parenchyma inadvertently excised along with the cyst wall.methods: We performed a retrospective study including 35 women who had undergone endometrioma cystectomy, using an ovarian tissue sparing procedure. In total 38 specimens were studied by three pathologists as three women presented bilateral localizations, and all cyst diameters measured at least 30 mm. For each endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
4
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 15 publications
0
77
4
12
Order By: Relevance
“…Both surgical procedures have previously been described elsewhere (2,(10)(11)(12). Neither requires antimesial incision of the ovarian parenchyma, as they can be performed through a small area of the cyst, free of ovarian tissue, which corresponds to the primary invagination spot of the cyst (13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both surgical procedures have previously been described elsewhere (2,(10)(11)(12). Neither requires antimesial incision of the ovarian parenchyma, as they can be performed through a small area of the cyst, free of ovarian tissue, which corresponds to the primary invagination spot of the cyst (13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
“…Recent data suggest that excising endometriomas by ovarian tissue-sparing cystectomy does not avoid inadvertent removal of ovarian parenchyma surrounding the cyst (1)(2)(3), particularly in enlarged cysts (2). Although several investigators have questioned whether the ovarian parenchyma immediately surrounding the cyst may still be functional (4), there is little doubt that postoperative fertility could be significantly impaired (5,6) by loss of ovarian cortex; this provokes the question as to whether pregnancy should be initiated before performing a cystectomy, whenever this scenario is possible.…”
mentioning
confidence: 99%
“…Surgery Severe ovarian damage and extensive follicle loss have been reported after cystectomy for endometriomas [11] resulting in a shorter reproductive life span [20,21], or even immediate ovarian failure as reported in few cases [19]. Table 1 shows the effect of surgery on ovarian reserve markers.…”
Section: Reduced Ovarian Reserve In Patients Affected By Endometriosismentioning
confidence: 99%
“…Nevertheless, it has also been shown that the endometrioma per se may cause damage to ovarian reserve and function. The thickness of ovarian tissue removed surgically seems to increase proportionally with cyst diameter [26]. Therefore, the reduction in volume of the endometrioma by low dose OCPs is crucial to preserve fecundity.…”
Section: Commentsmentioning
confidence: 99%